2020
DOI: 10.1177/1758835920911229
|View full text |Cite
|
Sign up to set email alerts
|

Widespread expression of Sonic hedgehog (Shh) and Nrf2 in patients treated with cisplatin predicts outcome in resected tumors and are potential therapeutic targets for HPV-negative head and neck cancer

Abstract: Background: Sonic hedgehog (Shh) and Nrf2 play a critical role in chemotherapeutic resistance. These two genes have been found to be dysregulated in head and neck squamous cell carcinomas (HNSCC). The purpose of this study was to analyze the expression, function and clinical prognostic relationship of Shh and Nrf2 in HNSCC in the context of therapeutic resistance and cancer stem cells (CSCs). Methods: We analyzed a cohort of patients with HNSCC to identify potential therapeutic biomarkers correlating with over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…HO-1, the Nrf2-targeted gene, was also elevated in cisplatin-resistant HNNC patients. Knockdown of Nrf2 reversed the sphere-forming efficiency that marks the cancer stem cell characteristics in FaDu cells [157]. Inhibition of Nrf2 by artesunate leading to a reversal of the ferroptosis resistance in cisplatin-resistant HNC cells has been reported [158].…”
Section: Targeting the Prx Antioxidant System In Hncmentioning
confidence: 99%
“…HO-1, the Nrf2-targeted gene, was also elevated in cisplatin-resistant HNNC patients. Knockdown of Nrf2 reversed the sphere-forming efficiency that marks the cancer stem cell characteristics in FaDu cells [157]. Inhibition of Nrf2 by artesunate leading to a reversal of the ferroptosis resistance in cisplatin-resistant HNC cells has been reported [158].…”
Section: Targeting the Prx Antioxidant System In Hncmentioning
confidence: 99%
“…As shown by Noman et al. ( 16 ) for an early diagnosis and prognosis of HNSCC, it is necessary to validate and explore the prognostic values of the key genes of the cancer. They used The Cancer Genome Atlas (TCGA) database analysis and performed the experimental validation of the widespread expression of Sonic hedgehog (Shh) and Nrf2 genes in HNSCC patients treated with cisplatin.…”
Section: Resultsmentioning
confidence: 99%
“…However, high expression of this gene is indispensable for oral SCC progression ( 77 ) and adaptation to nutrient deprivation and hypoxia ( 78 ), and may inhibit apoptosis. The other two genes, Nrf2 and Itga6, known to be promoting factors of chemoresistance, are overexpressed in the non-responders ( 15 , 16 ). The non-responders also showed overexpression of INMT and MYOM3, but their function in HNSCC remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Goto et al recently showed that increased expression of ATP Binding Cassette Subfamily B Member 1 (ABCB1, commonly known as MDR1) and NRF2 are associated with doxorubicin resistance of CD44 + CD133 + cells, but not in case of CD44 + and CD44 + CD133 − cells [ 153 ]. Noman et al recently reported that high expression of Sonic hedgehog and NRF2 correlates with induced stem cell-like characteristics and contributes to chemoresistance of HNSCC cells [ 154 ]. A very recent study showed that dexamethasone can induce chemosensitization of CSCs through reduced expression of NRF2 and consequently increased levels of ROS, but only after the treatment with gemcitabine and 5-fluorouracil [ 155 ].…”
Section: The Role Of Nrf2 In Cancer Stem Cellsmentioning
confidence: 99%